MicroRNA in Cervical Cancer: OncomiRs and Tumor Suppressor miRs in Diagnosis and Treatment - Kouji Banno; Miho Iida; Megumi Yanokura; Iori Kisu; Takashi Iwata; Eiichiro Tominaga; Kyoko Tanaka; Daisuke Aoki (The Scientific World Journal)
Cervical cancer is a female-specific disease with a high incidence and mortality. MicroRNAs (miRNAs) are implicated in posttranscriptional regulation of gene expression and in the pathogenic mechanisms of cancer, suggesting their importance in diagnosis and treatment. miRNAs may have roles in the pathogenesis of cervical cancer based on the increases or decreases in several specific miRNAs found in patients with this disease. The miRNAs implicated in cervical cancer are miR-21, miR-126, and miR-143, and clinical application of these miRNAs for diagnosis and treatment is under investigation. Methods for diagnosis of cervical cancer include analysis of changes in the levels of specific miRNAs in serum and determination of aberrant hypermethylation of miRNAs. Supplementation of miR-143 or inhibition of miR-21 activity in vivo may be therapeutic strategy for cervical cancer. Previous approaches to development of siRNA as a drug have provided information for establishment of therapy based on these approaches, and an anti-miR-21 inhibitor has been developed. miRNAs also have effects on drug resistance and may be useful in combination therapy with other drugs.